How people organise cultural attitudes: cultural belief systems and the populist radical right. Issue 4 (4th July 2017) - Daenekindt, Stijn; de Koster, Willem; van der Waal, Jeroen
Abstract: Political scientists generally agree that all individuals structure their cultural attitudes in the same unidimensional fashion. However, various populist radical right parties remarkably combine moral progressiveness with conservatism regarding immigration-related issues. This suggests that the structuring of cultural attitudes among the electorate may also be more complex than typically assumed. Applying Correlational Class Analysis to representative survey data, the study uncovers three cultural belief systems. For individuals adhering to an integrated one, all cultural attitudes are interdependent, as typically assumed. However, two alternative belief systems are also uncovered: intermediate and partitioned . In the latter, positions on one cultural attitude (e.g. ethnocentrism) are barely related to positions on others (e.g. rejecting Islam or opposing homosexuality). The existence of multiple cultural belief systems challenges the widely held assumption that all people organise their cultural attitudes similarly. Both political party agendas and individuals' education level and religion appear key to understanding variation in belief systems.